Behavioural and neurophysiological markers reveal differential sensitivity to homeostatic interactions between centrally and peripherally applied passive stimulation. Issue 6 (8th July 2013) - Gatica Tossi, M. A.; Stude, P.; Schwenkreis, P.; Tegenthoff, M.; Dinse, H. R.
Abstract Repetitive transcranial magnetic stimulation (rTMS) is an effective tool for inducing functional plastic changes in the brain. rTMS can also potentiate the effects of other interventions such as tactile coactivation, a form of repetitive stimulation, when both are applied simultaneously. In this study, we investigated the interaction of these techniques in affecting tactile acuity and cortical excitability, measured with somatosensory evoked potentials after paired median nerve stimulation. We first applied a session of 5‐Hz rTMS, followed by a session of tactile repetitive stimulation, consisting of intermittent high‐frequency tactile stimulation (iHFS) to a group of 15 healthy volunteers ("rTMS + iHFS" group). In a second group ("rTMS w/o iHFS"), rTMS was applied without iHFS, with a third assessment performed after a similar wait period. In the rTMS w/o iHFS group, the 5‐Hz rTMS induced an increase in cortical excitability that continued to build for at least 25 min after stimulation, with the effect on excitability after the wait period being inversely correlated to the baseline state. In the rTMS + iHFS group, the second intervention prevented the continued increase in excitability after rTMS. In contrast to the effect on cortical excitability, rTMS produced an improvement in tactile acuity that remained stable until the last assessment, independent of the presence or absence of iHFS. Our results show that these methods can interact homeostatically when used consecutively, and suggest that different measures of cortical plasticity are differentially susceptible to homeostatic interactions.